Current state of management of hiv-infected patients with digestive system comorbid pathology: analysis of physicians’ survey - Vysotskyi , Володимир (Psychosomatic Medicine and General Practice, 2020)
Introduction. The HIV epidemic, which affects millions of people in eastern Europe, remains one of the most important unresolved health issues. A patient-oriented approach to HIV-infected people improves the quality of medical care, affects the reliability of statistics, streamlines the planning and adequacy of public funds. The issues of comorbidity of the pathology of the digestive system in HIV infection and the formation of adherence to effective antiretroviral therapy (ART) are becoming particularly relevant. As a result, the role of family medicine practice in the detection, treatment, and management of gastrointestinal diseases in HIV-infected patients in Ukraine is growing. The purpose of the study: To study the role of general practitioners in family medicine in the examination and management of HIV-infected people with concomitant pathology of the digestive system. Material and methods. A survey was conducted among 200 general practitioners of family medicine (GPFM) and 292 physicians - limited specialists of a number of health care facilities in Kyiv and various regions of Ukraine by dint of a questionnaire developed through an internet survey and paper-based. Results and discussion. General practitioners of family medicine noted rather low participation in the monitoring of compliance and side effects of ART, as well as the management of concomitant pathology of the digestive system (DS) in HIV-infected patients. Most of the surveyed physicians noted the lack of clear algorithms for action in the development of clinical routes of HIV-infected patients with concomitant pathology of the DS and almost all respondents confirmed the feasibility of using in their current practice algorithms developed for such patients. The vast majority of GPFM didn’t fully know the ways of movement HIV-infected patients from diagnosis to a stable virological/immunological response and, thus, were not able to fully manage the concomitant pathology of DS. HIV-infected patients who underwent and reacted negatively to ART didn’t return to GPFM and therefore didn’t receive adequate, continuous, comprehensive, and coordinated medical care for various DS pathologies. Returning of HIV-infected patients from limited specialists to GPFM has been low, sporadic, which may explain the decline in the ability of GPFM’s to effectively monitor the clinical outcomes of treatment of DS pathology and ART therapy side effects. Conclusion. Find out some of the problems on detection of DS pathology in HIV-infected people and further management tactics of such patients have been clarified. Due to the inconsistency and insufficient volume of screening for comorbid pathology of the DS organs in HIV-infected patients, many chronic pathologies remain undetected in the practice of GPFM. The presence of untreated comorbid diseases of the DS organs in HIV infection may be a risk factor for reduced effectiveness of ART in such patients. Therefore, special attention of family physicians should be paid to the timely detection, treatment, and monitoring of HIV diseases in HIV-infected patients. It is considered expedient to introduce clear algorithms of joint actions of GPFM and limited specialists involved in the management of HIV-infected patients with concomitant DS pathology.